Leadership Theory, Leadership Functions, Leadership Approach and Quality of Educational Leadership at SMPIT Al Marwat Lemahabang - Muhamad Iqbal Albaqih; M. Asep Kuswara; Sandi Jafar; Tamsikuddin; Masduki Duriyat (al-Afkar, Journal For Islamic Studies, 2025)
Education requires effective leadership to improve the quality of education and teacher performance. Various leadership approaches such as transformational, transactional, situational, servant, and authoritarian have advantages and disadvantages. Relevant curriculum development, use of technology, effective communication, team leadership approach, and team effectiveness can help improve the quality of education. In synthesis, an effective leadership approach can help achieve educational goals by developing relevant curricula, innovative teaching methods, and adequate resources. A competent school principal can manage resources effectively and ensure that teachers can carry out their duties well. This research examines the theory, function, approach and quality of educational leadership at SMPIT Al Marwat Lemahabang. Using qualitative descriptive methods, this research explores aspects of leadership through interviews, observation and documentation. The research results show that effective leadership plays a crucial role in improving the quality of education. The leadership approach at this school includes collaboration and authoritative influence, with a tendency towards an authoritarian style in handling discipline. Leadership functions such as supervision, decision making, and motivation are found to be important in achieving organizational goals. This research highlights the importance of balance between assertiveness and collaboration in educational leadership, as well as the need to continuously develop leadership qualities to create an effective and superior learning environment.